Screening of N-Benzoyl Isoserine Methyl Ester (N-bime) for Anti-inflammatory Analgesic activity and Toxicity Profile in Animals: An Experimental Investigation - Niroomand, Maliha; U. Shah, Kalpana; Ghongane, Balasaheb B. (Research Aspects in Agriculture and Veterinary Science Vol. 5, 2022)
Background: Pain and inflammation are the basic processes involved in the pathogenesis of many diseases. Non-steroidal anti-inflammatory drugs are often used to treat rheumatic diseases. The study compound N-Benzoyl Isoserine Methyl Ester (N-bime) is a newly synthesized propionic acid derivative by National Chemical Laboratory, Pune. Since the biological data of this compound is not available, the present study has been planned to screen this compound for anti-inflammatory, analgesic activity and its toxicity profile in animals. Aims: The aim of this study was to screen N-bime for anti-inflammatory, analgesic and anti-pyretic activity in animals and to compare anti- inflammatory, analgesic and anti-pyretic activity if any of N-bime with Ibuprofen and to study its toxicity profile. Methods: Single dose toxicity study was carried out in rats. Anti-inflammatory activity was tested by Rat Hind Paw Oedema and Cotton Pellet Implantation method. For Analgesic activity, Acetic acid induced writhing and Tail Pinch method was used. Yeast induced Pyrexia was used for evaluation of anti-pyretic activity. Ibuprofen was the positive control. Data are presented as mean±SEM. Statistical analysis was performed by analysis of variance and students unpaired ‘t’ test. Results: The test compound N-bime did not show any apparent adverse effects or mortality in the dose range 1 mg – 500 mg / 100 gm body weight in animals. It showed better anti-inflammatory actions in higher doses as compared to Ibuprofen (p< 0.05). In acetic acid induced writhing test N-bime offered better protection against writhes, than Ibuprofen. But, both failed to demonstrate analgesic activity in the Tail Pinch method. N-bime showed a gradual decrease in temperature in the anti-pyretic test (P<0.001). Conclusions: The present study indicates that N-bime does possess anti- inflammatory, analgesic and weak anti-pyretic properties like the NSAIDs. It has proved to be safe in the dose range of 1mg – 500 mg / 100 gm body weight in rats and mice.